Augmented reality in healthcare since 2020: A systematic review of efficacy, safety, and workflow impacts - Alzahrani, Nouf Matar (Edelweiss Applied Science and Technology, 2026)
This study systematically reviews post-2020 evidence on the clinical efficacy, safety, and workflow implications of augmented reality (AR) in healthcare, addressing the lack of integrated, cross-domain synthesis as AR transitions from experimental use to real-world clinical deployment. Following PRISMA 2020 guidelines, five databases (PubMed, Scopus, Web of Science, IEEE Xplore, and Cochrane Library) were searched for peer-reviewed studies published between January 2020 and October 2025. Forty-one studies met the inclusion criteria. Methodological quality was assessed using Cochrane RoB 2, ROBINS-I, MMAT, and CASP tools. Due to substantial heterogeneity, findings were synthesized narratively. Across surgical, rehabilitative, educational, and diagnostic contexts, AR consistently improved procedural accuracy, learning outcomes, and workflow efficiency. Surgical studies reported error reductions of 15–46%, while rehabilitation studies showed functional gains in over 80% of cases. No serious adverse events were reported, although mild visual fatigue and cognitive load were noted with head-mounted displays. The evidence indicates that AR has matured into a clinically viable, safe, and workflow-enhancing technology when appropriately implemented. Healthcare organizations can leverage AR to improve precision, training efficiency, and care delivery, provided integration aligns with task complexity, user expertise, and workflow design.